Between will and necessity. The messianic subjectivism of Tzvetan Todorov and the revolutionary objectivism of Frantz Fanon - Alessandroni, Emiliano (Itinerari, 2023)
Todorov and Fanon are two intellectual figures engaged in a bitter denunciation of colonialism. In Todorov, however, this criticism tends to be accompanied by a dismissive judgment towards the entire Jacobin-Bolshevik tradition. Indeed the way in which the Bulgarian essayist holds together these two viewpoints (above all anti-colonialist and anticommunist) is through the adoption of a predominantly moral rather than political attitude in the face of great international conflicts, which gives rise to a sort of romantic anticolonialism, altogether abstract and susceptible to proceeding in a rather fragmentary way. His own philosophy, moreover, primarily focused on a hypostatic idea of “subjective will,” contributes to encourage and nourish such abstraction. Fanon holds a diametrically opposed perspective. At its core we find the concept of “objective necessity.” In the end, his anticolonialism appears not only much more uniform, systematic and coherent than Todorov’s, but ultimately, more realistic.